Attachement et changement dans un monde en transformation - Bousquet, François (éditions Quae, 2022)
Let's ask the question around us: "Why don't people change?" The answer will most often be: "because they are too attached to their privileges, traditions, achievements, relationships, cultures, lands, etc. They will never change! They will never change!" This theory that attachment prevents change is common sense. However, for many years, researchers who study the concept of attachment, and in particular attachment to place, have shown that this theory is not validated. On the contrary, attachment can provide security to individuals and support change. This book is based on lessons learned from the literature, as well as on transdisciplinary theoretical and methodological proposals. It is the result of interactions between researchers from different disciplines working in France, the UK, South Africa and Senegal. Reading this book will invite, stimulate and guide students, researchers, decision-makers, users, or anyone involved in processes of change in social and ecological systems in taking into account attachments and affective relationships to accompany transitions.